TI_GERICHTE 11.2010.101 vom 16. November 2012 , Cancellazione o riscatto di servitù inutilizzata per lungo tempo - TI Tribunale d'appello (2012)
Cancellazione o riscatto di servitù inutilizzata per lungo tempo